Complete coding sequence characterization and comparative analysis of the putative novel human rhinovirus (HRV) species C and B - Linsuwanon, Piyada (BioMed Central, 2011)
BACKGROUND: Human Rhinoviruses (HRVs) are well recognized viral pathogens associated with acute respiratory tract illnesses (RTIs) abundant worldwide. Although recent studies have phylogenetically identified the new HRV species (HRV-C), data on molecular epidemiology, genetic diversity, and clinical manifestation have been limited. RESULT: To gain new insight into HRV genetic diversity, we determined the complete coding sequences of putative new members of HRV species C (HRV-CU072 with 1% prevalence) and HRV-B (HRV-CU211) identified from clinical specimens collected from pediatric patients diagnosed with a symptom of acute lower RTI. Complete coding sequence and phylogenetic analysis revealed that the HRV-CU072 strain shared a recent common ancestor with most closely related Chinese strain (N4). Comparative analysis at the protein level showed that HRV-CU072 might accumulate substitutional mutations in structural proteins, as well as nonstructural proteins 3C and 3 D. Comparative analysis of all available HRVs and HEVs indicated that HRV-C contains a relatively high G+C content and is more closely related to HEV-D. This might be correlated to their replication and capability to adapt to the high temperature environment of the human lower respiratory tract. We herein report an infrequently occurring intra-species recombination event in HRV-B species (HRV-CU211) with a crossing over having taken place at the boundary of VP2 and VP3 genes. Moreover, we observed phylogenetic compatibility in all HRV species and suggest that dynamic mechanisms for HRV evolution seem to be related to recombination events. These findings indicated that the elementary units shaping the genetic diversity of HRV-C could be found in the nonstructural 2A and 3D genes. CONCLUSION: This study provides information for understanding HRV genetic diversity and insight into the role of selection pressure and recombination mechanisms influencing HRV evolution.